2019
DOI: 10.1016/j.ebiom.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Redefining malignant pleural mesothelioma types as a continuum uncovers immune-vascular interactions

Abstract: Background: Malignant Pleural Mesothelioma (MPM) is an aggressive disease related to asbestos exposure, with no effective therapeutic options. Methods: We undertook unsupervised analyses of RNA-sequencing data of 284 MPMs, with no assumption of discreteness. Using immunohistochemistry, we performed an orthogonal validation on a subset of 103 samples and a biological replication in an independent series of 77 samples. Findings: A continuum of molecular profiles explained the prognosis of the disease better than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 41 publications
(70 reference statements)
9
57
0
Order By: Relevance
“…They also have a strong prognostic value and may be of interest for guiding therapeutic strategies (38,39). Another recent publication further sustained that MPM heterogeneity is better described by a continuum (40).…”
Section: Mesothelioma Heterogeneitymentioning
confidence: 97%
“…They also have a strong prognostic value and may be of interest for guiding therapeutic strategies (38,39). Another recent publication further sustained that MPM heterogeneity is better described by a continuum (40).…”
Section: Mesothelioma Heterogeneitymentioning
confidence: 97%
“…These E/S.scores are highly associated with the prognosis and may have an impact on personalized therapeutic strategies in MPM, particularly targeted therapies and immunotherapies (Blum et al , 2019). A recent publication has also shown that MPM heterogeneity is well described by a continuum (Alcala et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 33–37 These studies use different techniques such as Nanostring technology, 34 mass cytometry, 33 or RNA-sequencing. 36 The diversity of obtained results suggests that the composition and role of the tumor microenvironment in MPM is remarkably complex and controversial, and thus further studies will contribute to elucidate this question.…”
Section: Discussionmentioning
confidence: 99%